Biomechanical structure of sprint start and effect of biological feedback methods on sprint start performance - İlbilge Ozsu (Türk Spor ve Egzersiz Dergisi)
One of the profound factors that affect sprint performance of athletes is the transfer of the possible highest propulsive force onto the starting blocks using an ideal sprint start body position. Hence, in the literature, there are a great deal of studies related to assessment and improvement of sprint start performance. In this review, evaluation of the literature based on improving the sprint start performance and sharing obtained instructions with sport scientists, trainers and athletes were aimed. According to the literature knowledge, it is stated that higher propulsive force onto the starting block and acceleration are two most important factors affecting on the results of sprint running. Also, it is rational to state that permanent kinesthetic awareness of individualized sprint start position could lead to significant improvements in sprint performances. For this reason, biofeedback trainings will be useful methods that provide a kinesthetic awareness of individualized sprint start position for athletes. Thus, athletes increase the probability of learning motor skill when they have opportunity to compare the actual motor performance output with expected ideal performance output. It is stated that motor skill acquisition level of athletes increases considerably if feedback is provided appropriately. Accordingly, the aim of this review is to present literature based knowledge about biomechanics of sprint start and effects of biological feedback methods on sprint start performance.